A case for the integration of comprehensive sexuality education in English language teacher education - Bonadeo, Flavia; Banegas, Darío; Monasterio, Sabrina; Tomatis, José Manuel; Berardo, Pablo (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
Comprehensive sexuality education continues to gain ground in Argentina and across countries. Sitting at the intersection of initial teacher education and TESOL, the aim of this paper is to describe and reflect on the initiative carried out by a teacher educator who imbued an initial English language teacher education programme in Argentina with a gender perspective to respond to a national law, the UN and UNESCO calls for sustainable actions. The voices of the teacher educator and three student-teachers constitute the backbone of this article as they articulate their lived experiences.